Mediation Model of Islamic Financial Inclusion in The Relationship Between Financial Literacy and Women’s Empowerment in the Halal Tourism Industry in Lombok - Ahadiah Agustina; Novi Yanti Sandra Dewi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to examine the role of Islamic financial inclusion as a mediating variable in the relationship between Islamic financial literacy and women's empowerment in the halal tourism sector in Lombok, West Nusa Tenggara. A quantitative method with an explanatory design was employed to analyze causal relationships among the variables. Data were collected through a questionnaire survey targeting women entrepreneurs in micro, small, and medium enterprises (MSMEs), and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that financial literacy has a significant effect on Islamic financial inclusion, and financial inclusion significantly contributes to women’s empowerment. Furthermore, financial inclusion is proven to act as a mediator that strengthens the relationship between financial literacy and women’s empowerment. These results confirm that improving financial literacy does not directly enhance empowerment, but rather operates through optimizing access to and utilization of Islamic financial instruments.